PORSI DAN NUTRISI MAKANAN MUHAMMAD SAW Kajian Hadis Teks dan Konteks - Mir’atun Nisa’ (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2016)
The primary factor in increase of fatness and obesity in Indonesia is food consumption pattern. This article is focused on assessing the nutritional intake of Muhammad based on hadis. By using thematic and nutritional science approach reflected the number of calories of the food of prophet Muhammad. The result can be a reference for muslims to balancing portions and nutrition also taking the purpose behind it.